GIS development for ground deformation data management. A case study in Cephallonia island (western Greece) - Vassilopoulou, S.; Chousianitis, K.; Sakkas, V.; Damiata, B.; Lagios, E. (Bulletin of the Geological Society of Greece, 2007)
The present study is concerned with the management of multi-thematic geo-data of Cephallonia Island, related to crustal deformation. A large amount of heterogeneous data (vector, raster, ascii files) involving geology, tectonics, topography, geomorphology and DGPS measurements was compiled. Crustal deformation was studied using GPS network consisting of '23 stations. This was installed and measured in October 2001 and re-measured during September 2003 following the Lefkas earthquake of August 2003 (Mw=6.2), and also in July 2006. With proper spatial analysis, a large number of thematic and synthetic layers and maps were produced. Simultaneously, a GIS Data base was organized in order to make an easy extraction of conclusions in specific questions.